Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1177/0960327113499167
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen treatment and N-acetylcysteine ameliorate acetaminophen-induced liver injury in a rat model

Abstract: An overdose of acetaminophen (APAP) produces centrilobular hepatocellular necrosis. We aimed to investigate the hepatoprotective effects of N-acetylcysteine (NAC) only and hyperbaric oxygen (O(2)) treatment (HBOT) combined with NAC, and their anti-inflammatory properties in liver tissue. In the current study, a total of 32 male Sprague Dawley rats were divided into 4 groups: sham, APAP, NAC, and NAC + HBOT. In the APAP, NAC, and NAC + HBOT groups, liver injury was induced by oral administration of 1 g/kg APAP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
(71 reference statements)
2
11
0
Order By: Relevance
“…Similarly, curcumin significantly inhibited the rise in AST, ALT and ALP by (52.8%, 37.08% and 41.8%) as compared to the relative acetaminophen group values. The previous results are in accordance with the results of previous researchers who demonstrated that these increases in liver enzymes were reduced by the administration of curcumin [38] and N-acetylcysteine [39].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, curcumin significantly inhibited the rise in AST, ALT and ALP by (52.8%, 37.08% and 41.8%) as compared to the relative acetaminophen group values. The previous results are in accordance with the results of previous researchers who demonstrated that these increases in liver enzymes were reduced by the administration of curcumin [38] and N-acetylcysteine [39].…”
Section: Discussionsupporting
confidence: 92%
“…Drug toxicity can also induce an inflammatory response through the production of cytokines by KCs and neutrophils, such as TNF-α, IL-6, IL-1β, IL-1α, and IFN-γ that modulate intracellular events [ 162 ]. These cytokines sensitize hepatocytes to biochemical stress, or regulate the adaptive immune-mediated cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies reporting the roles of NAC in APAP-induced liver injury. According to the study of Taslipinar et al (2013) [ 162 ] ( Table 2 ) that evaluated the hepatoprotective effects of NAC in an overdose of APAP producing centrilobular hepatocellular necrosis in rats, it was observed that doses of 100 mg/kg/day, i.p. for 5 days, significantly reduced hepatic TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HBO therapy has been used for carbon monoxide (Tilney, 2011;Weaver et al, 2002) and other types of intoxication (Youngster et al, 2010;Taslipinar et al, 2013). However, the mechanism of the beneficial effect has not been established.…”
Section: Discussionmentioning
confidence: 99%